Characterization of CuInS2 thin films prepared by one-step electrodeposition - Di Iorio, Yesica Dolores (2014)
CuInS2 thin films were fabricated by one-step electrochemical deposition from a single alkaline aqueous solution and using conductive glass as the substrate. The electrolyte consisted in 0.01 mol L-1 CuCl2, 0.01 mol L-1 InCl3, 0.5 mol L-1 Na2SO3 and 0.2 mol L-1 Na3C3H5- O(COO)3 (CitNa) at pH 8. The films were analyzed using a variety of techniques such as X-ray diffractometry, micro- Raman spectroscopy, X-ray energy dispersive spectroscopy, X-ray photoelectron spectroscopy and photoelectrochemistry. After carrying out a thermal treatment in sulfur vapor, chalcopyrite CuInS2 thin films were obtained. Etching the films in KCN solution was found to be a key step, enabling a final adjustment in the stoichiometry. These thin films exhibited p-type semiconductor behavior with the bandgap of 1.43 eV. The results show that electrodeposition provides a cost-effective and versatile method for the preparation of thin films of CuInS2, even when acidic precursors need to be avoided.